2018
DOI: 10.18174/452306
|View full text |Cite
|
Sign up to set email alerts
|

Sociaal-economische gevolgen van een totaal verbod van pulsvisserij voor de Nederlandse visserijsector

Abstract: of op www.wur.nl/economicresearch (onder Wageningen Economic Research publicaties).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The ban on pulse fishing in 2021 had profound consequences for the pulse fishers, as they had to revert back to beam trawling. Revenue was estimated to become negative with an annual loss of 100.000-120.000 Euro per vessel (Zaalmink et al 2018). The economic data for 2022 confirmed that the beam trawl fishery was making losses (Fig.…”
Section: Socio-economic Consequencesmentioning
confidence: 91%
“…The ban on pulse fishing in 2021 had profound consequences for the pulse fishers, as they had to revert back to beam trawling. Revenue was estimated to become negative with an annual loss of 100.000-120.000 Euro per vessel (Zaalmink et al 2018). The economic data for 2022 confirmed that the beam trawl fishery was making losses (Fig.…”
Section: Socio-economic Consequencesmentioning
confidence: 91%
“…For the calculation of the values, the following steps have been taken: is a system in the Dutch fishery where crew members earn a share of the landing value for each day they sailed along (Zaalmink, 2018).…”
Section: Buyout Value = ((Average Net Profit + Share Wage Of the Owner) -Alternative Income) * Capitalization Factormentioning
confidence: 99%
“…Deze visserij wordt op grote delen van de Noordzee uitgevoerd en het is dus niet verwonderlijk dat deze visserij het meest wordt geraakt door de sluiting van de gebieden. Het pulsverbod heeft geleid tot een afname van het financieel resultaat van bedrijven die moesten overstappen op het vissen met wekkerkettingen (Zaalmink, Hoekstra, Mol, & Strietman, 2018), waarbij er nu ook andere factoren kunnen zijn waardoor het lastig is om tot een goed verdienmodel te komen. Ook wanneer een variant maar tot een geringe afname van de omzet van deze bedrijven leidt, dan kan het zijn dat er grote consequenties zijn.…”
Section: Effecten Op De Tongvisserijunclassified